Pengaruh Intensitas Kebisingan Terhadap Tingkat Stres, Gangguan Kesehatan Pendengaran dan Kinerja Karyawan pada PLTD Nusa Penida - Billy Ardiwantoro; Tatan Sukwika; Hariyadi B Sukamdani (Cakrawala Repositori IMWI, 2023)
PLTD Nusa Penida is one of the Private Owned Enterprises in Klungkung Bali, which was established to meet the electricity needs of the surrounding community. The use of diesel engines as the main tool to help the process of electricity generation operational activities certainly creates noise that can interfere with the hearing process of employees, especially if it happens every day and takes place continuously. Therefore, it can be ascertained that employees who work in the Nusa Peninda PLTD field have a high risk of noise disturbance. The purpose of this study is to determine and analyze the effect of noise intensity on work stress levels, hearing health problems and employee performance. The method used is a quantitative approach with the type of exploratory research. The sample amounted to 35 people. The results of the study concluded that (1) noise intensity affects the hearing health problems of employees of PLTD Nusa Penida Bali. (2) Noise intensity does not affect the health problems of employees of PLTD Nusa Penida Bali. (3) Employee hearing health problems do not affect the performance of PLTD Nusa Penida Bali employees, and (4) Employee stress levels affect the performance of PLTD Nusa Penida Bali employees.